(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Dinara R. Valeeva (Kazan, Russian Federation) Concept is one of the basic terms in modern language studies. It is one of the key elements of language related not only to linguistic categories, but also to human consciousness. Concept can be defined as a dynamic mental structure mediating between man and the world, combining conceptual, value and cultural information realized in the verbal units of a certain language. Being complex mental units, concepts provide a basis for the mutual understanding between people of different linguacultures. However, the question of description of the concept and its status in modern science is complex and still not resolved. The author considers that concepts are usually verbalized in language. Any concept can be verbalized by lexeme, word combination, sentence and phraseological unit, proverb, discourse. Concept is ambiguous and multidimentional unit and it seems perspective to use the complex method of its research that include not only the analysis of its key words and paradigmatic and syntagmatic links of its nominees, but also the study of various types of discourses. The given article is devoted to the problem of actualization of the linguacultural concept “House / Home” in the works of the contemporary Russian writer L. Ulitskaya, whose works are created in the framework of “new women’s prose” – prose written by a woman and related to women. Analysing of the verbalization of the concept “House / Home” in the discourse of L. Ulitskaya, the author comes to the following conclusions. In the textual space of L. Ulitskaya, when the studying concept is being represented, the lexeme дом is usually used to designate a family. The explication of the concept “House / Home” is characterized by attributive phrases of positive emotions. Analysis of the syntagmatic relations of the word дом in the texts of L. Ulitskaya made it possible to reveal such cognitive features of the concept “House / Home” as «size of construction», «appearance», «time of construction», «belonging to the house», «relationships between family members». And lexical representatives of the studied concept permitted to make the conclusion about the expansion of the scope of the concept “House / Home”. In L. Ulitskaya’s texts the concept “House / Home” gets an expansive meaning due to additional cognitive features and figurative components. As a consequence, the peripheral interpretation zone of the studied concept is increasing. Key words: concept, culture, opposition, lexeme, seme, meaning, verbalization, representative, conceptual character (attribute). DOI 10.23683/1995-0640-2019-1-50-57